Pathological and immunohistochemical evaluation of wound healing potential of Nigerian bee propolis in albino rats (2018)
This study evaluated the efficacy of the Nigerian bee propolis as a wound healing agent, on full thickness skin wounds of healthy adult male (150.0 ± 0.5 g) albino rats randomly divided into three treated groups (propolis extract (PE), propylene glycol (PG), silver sulfadiazine) and an untreated group. Each rat had three circular full thickness skin wounds created on the cranial, middle, and caudal surface of the rat’s dorsum. The wounds in each group were topically treated with bee propolis extract (PE, 0.1 ml), propylene glycol (PG, 0.1 ml) and silver sulfadiazine (SS, 0.1 ml) twice daily for 21 days, except the untreated group (UT). The wounds were evaluated for gross (exudation, edema, hyperemia, wound contraction), histologic (granulation, angiogenesis, fibroplasia, epithelialization), and expression of epidermal growth factor (EGF) using standard techniques. Data was descriptively summarized as percentages, mean and analyzed using Chi-square and analysis of variance at α = 0.05.Wound edge edema (WEE), hyperemia, and exudation were prominent in all the groups between days 0–2.WEE was significantly less on day 3 in the PE (14%) and SS (14%) groups, compared with the PG (35%) and UT (66%) groups. Wounds treated with PG and UT were significantly more hyperemic than those with PE and SS. Wound contraction was significantly less on day 2 in the UT wounds when compared to the treated wounds (PE = 12.63%, SS = 2.22%, PG = 4.94%, and UT = − 2.82%). The wound contraction was remarkable between days 4–8 in the PE- and SS-treated wounds (PE > SS > PG > UT). The microscopic changes at days 4, 8, 12, 16, and 21 showed significant evidence of epithelial proliferation, improved angiogenesis, granulation, and fibrous connective tissue in the PE- and SS-treated rats compared with the negative controls. The inflammatory response showed that the PE group had the highest amount of macrophages and leucocytes on day 4 with the trend being PE > SS > PG > UT. Neutrophils regressed in the treated wounds on day 8 but were consistently high in the untreated group from days 4–16. The immunohistochemical evaluation showed that the intensity of EGF was consistently high in the SS- and PE-treated wounds. Nigerian bee propolis extract accelerated wound healing similar to that of silver sulfadiazine based on wound healing indices and is therefore recommended for the management of wounds especially in low-income communities where propolis is available and affordable